2017
DOI: 10.1080/07357907.2017.1303505
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the p53-DNA Complex by the Nuclear Protein Dmp1α

Abstract: We recently reported the existence of a physical interaction between the Myb-like transcription factor Dmp1 (Dmtf1) and p53 in which Dmp1 antagonized polyubiquitination of p53 by Mdm2 and promoted its nuclear localization. Dmp1 significantly stabilized p53-DNA complexes on promoters that contained p53-consensus sequences, which were either supershifted or disrupted with antibodies to Dmp1. Lysates from mice injected with doxorubicin showed that Dmp1 bound to p21Cip1, Bbc3, and Thbs1 gene regulatory regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…Our study shows that the Dmp1 protein directly interacts with p53 and blocks the activities of Mdm2, especially in epithelial cells and T lymphocytes (42). Dmp1 also stabilizes p53 binding to transcriptional target genes (43). These two mechanisms will act synergistically to boost the p53 activity to prevent tumorigenesis.…”
Section: Future Directions For Researchmentioning
confidence: 74%
See 3 more Smart Citations
“…Our study shows that the Dmp1 protein directly interacts with p53 and blocks the activities of Mdm2, especially in epithelial cells and T lymphocytes (42). Dmp1 also stabilizes p53 binding to transcriptional target genes (43). These two mechanisms will act synergistically to boost the p53 activity to prevent tumorigenesis.…”
Section: Future Directions For Researchmentioning
confidence: 74%
“…Dmp1α expression antagonized p53's ubiquitination by HDM2 both in cell and in vitro, and restores p53's nuclear localization that was lost with HDM2 expression (42). Moreover, Dmp1α stabilized p53-DNA complexes on genomic DNA that contained p53-consensus sequences, which were either supershifted or disrupted with antibodies to Dmp1 (43). Dmp1α-p53 interaction significantly increased the levels of p53 independent of Dmp1's DNA-binding, and hence the p21 Cip1 promoter activity was synergistically induced by co-expression of Dmp1α and p53 in p53 −/− ;Arf −/− double knockout cells (42).…”
Section: Dmp1-interacting Proteinsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to ETS1 , loss of the Myb-like transcription factor DMP1α ( DMTF1α ) binds to the Ets site in the Arf promoter (91) is associated with low Ki67 and is associated with favorable prognosis (92) for Dmp1 original articles; 93101; 67, 102106 for reviews). Dmp1α also binds directly to p53 for activation in Arf -deficient cells (100, 101). It was reported that expression of neuNT, but not normal neu, caused transcriptional activation of Ets, AP1, or NF-κB-dependent reporter genes (107).…”
Section: Ets1 and Ets2mentioning
confidence: 99%